Some Remarks About the Translation of Yun Lintang Yinshi Zhidu Ji Published in PPC 60 - Sabban, Françoise (Petits Propos Culinaires, 1999)
Readers who enjoyed the translation (in PPC 60) by Teresa Wang and EN Anderson of the culinary work by the 14th century Chinese artist Ni Tsan, and who are glad to have this work on their shelves for subsequent reference, will welcome the additional comments, and proposed corrections, which have been provided by Françoise Sabban, a French professor who has specialized in Chinese food and cuisine. In what follows, words printed in bold type represent the proposed corrections.